EFEKTIVITAS MICROSOFT TEAMS TERHADAP HASIL PEMBELAJARAN IPA PADA MASA PANDEMI COVID-19 - Titiek Yusfriyanti (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
Microsoft Teams as a learning platform that allows teachers and students to collaborate and interact during online learning. This study aims to determine the effectiveness of implementing Microsoft Teams as a learning platform during the Covid-19 pandemic at SMP Negeri 44 Surabaya. The method used in this research was quantitative which was analyzed in statistical form. Based on the data obtained, it showed that the use of Microsoft Teams consists of three indicators, namely the ease of access to Microsoft Teams which results in a presentation value of 80.5, understanding of learning material using Microsoft Teams gives a presentation score of 82 and excellence when using Microsoft Teams. The result of the value presented was 78. Of the three indicators, the average total percentage is 80.16% which is said to be effectively used in Science learning (IPA). For the effectiveness of using Microsoft Teams in learning, it is appropriate for this purpose and Microsoft Teams significantly affects the learning outcomes of grade 9F students at SMP Negeri 44 Surabaya in the 2020/2021 academic year.